2022
DOI: 10.52965/001c.37782
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Enhancement of Rotator Cuff Repair: A Narrative Review

Abstract: Introduction As rotator cuff repairs (RCRs) are among the most common procedures in upper extremity orthopedics, healing augmentation using pharmacologic enhancement of the repaired rotator cuff muscle is of particular interest. Objective The purpose of this study is to review the current understanding of Matrix Metalloproteinases (MMPs), Doxycycline, Testosterone, Estrogen, Growth hormone/ IGF-1, Vitamin D, and Vitamin C as a means to mitigate deleterious effects and propagate factors that support healing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Another possibility for increasing the contribution of IGF-1 to tendon repair is the use of an IGF-1-embedded matrix. In a study on IGF-1 pegylation, the researchers used a copolymer matrix based on poly(L-lactide)-copoly(ε-caprolactone) with various modifications of embedded IGF-1 in a rat model of a rotator defect [131]. Application of the PEG-IGF-1m matrix led to enhanced in the biomechanical properties of the tissue.…”
Section: Insulin-like Growth Factor (Igf-1)mentioning
confidence: 99%
“…Another possibility for increasing the contribution of IGF-1 to tendon repair is the use of an IGF-1-embedded matrix. In a study on IGF-1 pegylation, the researchers used a copolymer matrix based on poly(L-lactide)-copoly(ε-caprolactone) with various modifications of embedded IGF-1 in a rat model of a rotator defect [131]. Application of the PEG-IGF-1m matrix led to enhanced in the biomechanical properties of the tissue.…”
Section: Insulin-like Growth Factor (Igf-1)mentioning
confidence: 99%
“…Oxidative stress significantly influences the pathophysiological mechanisms of osteoporosis and tendinopathy co‐morbidities, highlighting antioxidant therapy as a potential treatment approach. 9 , 19 We have thoroughly explored how oxidative stress contributes to osteoporosis and tendon diseases. Next, let's delve into how antioxidants function in the treatment of these diseases and their impact on human health.…”
Section: The Potential Therapeutic Value Of Antioxidants In the Co‐mo...mentioning
confidence: 99%
“… 17 , 18 Early‐stage tendinopathy is usually managed with conservative treatments like medication, mechanical loading and shockwave therapy, whereas more advanced cases may require surgical intervention. 19 , 20 However, conservative treatments often provide only temporary relief, and surgery carries risks like infection, joint stiffness, and the possibility of tendon re‐tearing, significantly impacting the patient's quality of life. 21 , 22 The high incidence of tendinopathy, its stubborn nature, and the risk of permanent functional damage contribute to a substantial economic burden globally.…”
Section: Introductionmentioning
confidence: 99%
“…Testa et al performed an insurance database study and determined that patients prescribed testosterone had a significantly elevated risk for to undergoing a RCR as well as a re‐repair suggesting patients deficient in testosterone requiring treatment may be at‐risk for rotator cuff tearing 20 . Testosterone has been shown to increase tendon stem cell number and differentiation while estrogen agonists have been shown to decrease muscle atrophy in the setting of chronic rotator cuff tears 21 . We previously established a murine model of RCR and demonstrated that a potent estrogen receptor agonist (diethylstilbestrol) improved the healing based on histological and molecular analyses 17,22 .…”
Section: Introductionmentioning
confidence: 99%
“…20 Testosterone has been shown to increase tendon stem cell number and differentiation while estrogen agonists have been shown to decrease muscle atrophy in the setting of chronic rotator cuff tears. 21 We previously established a murine model of RCR and demonstrated that a potent estrogen receptor agonist (diethylstilbestrol) improved the healing based on histological and molecular analyses. 17,22 We have shown an association between sex hormone deficiency and the requirement for RCR utilizing a large insurance database.…”
mentioning
confidence: 99%